Differential Changes of Proline Content and Activities of Antioxidant Enzymes Results in Varied Salt-Tolerance in Canola Genotypes - Hajar Ghorbannejad; Rayhaneh Amooaghaie (Journal of Genetic Resources, 2017)
Saline soils and saline irrigation waters present potential hazards to canola production. Therefore, in this study in order to find indicators for salt tolerance, the changes of proline content and the activities of antioxidant enzymes were investigated in two canola genotypes (H308, H420) under various salt concentrations (0, 50, 100, 150 and 200 mM). Results showed that compared to the control, salinity reduced seed germination and biomass of plants and caused the significant increase in proline content and lipid peroxidation in leaves of both genotypes. On the basis of growth parameters, H420 was more salt sensitive than H308. H308 accumulated higher proline contents and had higher antioxidant enzyme activities (SOD, POX, APX, and CAT) than H420 especially at higher salinity levels. The activities of POX, APX, and CAT in H420 slightly increased in low salinity levels but in high salinity, their activities decreased and return to less or same level of the control. The differences in proline accumulation ability and the activities of antioxidative enzymes in leaves, at least in part, explained greater tolerance of H308 to salt stress than H420.